Description Of Risk Factors For Nosocomial Infection In Post-Operative Wounds In Banten Province Hospital Surgery Rooms, 2023 - Mulyati (PROFESSIONAL HEALTH JOURNAL, 2024)
Nosocomial infections are microorganisms that enter the human body which are caused by various factors including gender, age, comorbidities, length of treatment, whether or not the patient is crowded in the room which causes nosocomial infections in post-operative wounds at the Banten Provincial Hospital in 2023. The high rate of nosocomial infections in hospitals throughout the world is 7.1% per year or 190 million patients are treated annually. Meanwhile, in Indonesia itself, data on nosocomial infections can be seen from surveillance data carried out by the Indonesian government ministry of health in 2015. Data on nosocomial infections was quite high, namely 6 - 16% with an average of 9.8% of post-operative patients experiencing nosocomial infections. while being treated. The aim of this research is to determine the incidence and description of risk factors for nosocomial infections in post-operative wounds at Banten Hospital in 2023. The research method used is descriptive research with observation techniques, random sampling. The incidence of nosocomial infections is influenced by gender, age, comorbidities, length of stay, whether or not the patient's room is crowded which causes nosocomial infections.